Compreensão de palavras, frases e texto em alunos dos primeiros anos do Ensino Fundamental - Machado, Márcia Di Santo de Melo (2016)
Studies grounded on Cognitive Psychology aim to understand the cognitive and the linguistic processes involved in how to teach and how to learn to read. The goal of this research was to check how a group of students from Elementary School evolves on reading comprehension in a regular situation of teaching. 98 students took part of this study, from 2nd, 3rd and 4th grades of elementary school of a private school located in the city of Santo André, in the state of São Paulo. Four instruments were used: School Performance-Words Reading Test (TDE); Words Recognition Task (TRP); Reading Test and Comprehension of Sentences (TELCS) and Cloze Technique (TC). Analysis about the evolution of reading abilities and words, sentences and text comprehension were made, comparing the results of the students from 2nd, 3rd and 4th grades and comparative analysis of the results from boys and girls. It was used: average, standard deviation, T-student, ANOVA and Tukey. The results show the students’ development from 2nd to 4th grades of Elementary School on words, sentences and text comprehension. No differences on words, sentences and text comprehension between boys and girls were found